The risk of respiratory symptoms near power stations among 15-17 year-old students in Cyprus, 2006-07 - Yiallouros, Panayiotis K.; Middleton, Nicos; Zeniou, Maria; Economou, Mary; Kolokotroni, Ourania; Pipis, Spiros D. (My University, 2009)
Exposure to air pollutants has been repeatedly shown to be associated with a range of adverse respiratory effects. Differences in asthma prevalence on an island the size of Cyprus may reflect such environmental factors. This study assessed the geographical distribution of self-reported asthmatic symptoms in 15-17-year old participants recorded in an ISAAC survey across Cypriot schools (N=6393). Using GIS software, circular zones were constructed around each of the three power stations on the island in increments of 5km. vidence of an increased risk among participants with regards to their community’s proximity to the source of emissions was investigated in logistic regression models before and after adjusting for person-based risk factors, co-morbidity and intradistrict correlation. Adjusted odds ratio for active asthma was 1.79 (95%CI: 1.27, 2.53) among residents in the 5km radius compared to those more than 30km away with no evidence, however, of a dose-response relationship at intermediate distances.
Keywords: Air pollution; Asthma; Geographical Information Systems; Mapping; Power Stations; Respiratory morbidity